Nurses' and Physicians' Distress, Burnout, and Coping Strategies During COVID-19: Stress and Impact on Perceived Performance and Intentions to Quit. Issue 1 (10th May 2022) - Lou, Nigel Mantou; Montreuil, Tina; Feldman, Liane S.; Fried, Gerald M.; Lavoie-Tremblay, Mélanie; Bhanji, Farhan; Kennedy, Heather; Kaneva, Pepa; Harley, Jason M.
Abstract : Introduction: Health care providers (HCPs) have experienced more stress and burnout during COVID-19 than before. We compared sources and levels of stress, distress, and approaches to coping between nurses and physicians, and examined whether coping strategies helped mitigate the negative impact of stress and intentions to quit. Methods: Using a cross-sectional study design, burnout was measured with the Maslach Burnout Inventory. Psychological distress was measured using the Depression, Anxiety, and Stress Scale. A self-reported survey was used to evaluate stressors, impact on perceived performance, and intentions to quit. The data were analyzed using t -tests and linear regression models. Results: Responses of 119 HCPs were analyzed. Findings suggest that (1) compared to physicians, nurses experienced a higher level of distress and burnout, and used more maladaptive coping strategies. (2) Both nurses and physicians experienced more distress and burnout during COVID-19 than before. (3) Adaptive coping strategies moderated the negative impact of stress on work performance (4) Adaptive coping strategies moderated the negative effect of stress on burnout, which in turn reduced intentions to quit. Stress negatively impacted work performance and burnout only for those with low, but not high, levels of adaptive coping strategies. Discussion: The current findings of HCPs' challenges, risks, and protective factors provide valuable information (1) on COVID-19's impact on HCPs, (2) to guide the distribution of institutional supportive efforts and recommend adaptive coping strategies, and (3) to inform medical education, such as resilience training, focusing on adaptive coping approaches.